Understanding Energy Practices in Ghanaian Higher Education: Lessons from Academic City University - Budu, Bismark; Oluwatito Fadayiro, Jordan; Lamptey, Enoch; Mensah, Michael (IIUM Journal of Educational Studies, 2025)
This research illuminates the imperative for strategic energy management within the higher education sector, as evidenced by the multifaceted challenges and opportunities elucidated across diverse university contexts. The comprehensive data collection efforts provided valuable insights into energy consumption patterns among various stakeholders, ranging from students and faculty to staff members locally. Moreover, the methodological rigor employed in data acquisition and analysis at Academic City University underscores the percentage of about 95% of staff, student and faculty having knowledge about energy management, only about 65% really practice effect energy management and hence the formulation of evidence-based policies and strategies for effective energy management. By leveraging these insights, universities can develop targeted interventions to optimize resource allocation, mitigate financial burdens, and foster a culture of energy consciousness and stewardship.